PENGARUH MODEL LATIHAN TERHADAP KEMAMPUAN UNDERWATER DOLPHIN KICK ATLET PR GARUDA LAUT MAKASSAR - Rusli, Kurnia; Ferawati, Ferawati (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi STKIP Mega Rezky Makassar, 2018)
Undewater dolphin kick is technique that affects speed in butterfly stroke. aims of this research is to know affect of half squat jump, stretching PNF and aerobic training models to undewater dolphin kick speed. The methode applied is experiment with one group pretest-posttest design. The sample is 20 men and 10 women Garuda Laut Makassar swimming Club Athlete. This study was obtained 0.924 with a value of 0.000 less than 0.05 of α value. It means that training models program in 16 meets has significant affect to underwater dolphin kick of Garuda Laut Makassar swimming Club Athlete. As well as average of 15.89 : 13,69 that shows 2.29 second as an increase of speed after training of PNF stretching, half squat jump and aerobic training to underwater dolphin kick speed of Garuda Laut Makassar swimming Club Athlete.